Sistem Tracking Matahari Menggunakan Solar Cell Berbasis Mikrokontroler ATmega16 - Heru Nugroho; Supriyana Nugroho (Politeknosains, 2019)
Energy is a very important requirement because all activities require energy. Energy sources have been found to meet human needs. Energy sources are divided into 2, which can be updated and cannot be updated. Energy sources that can be updated are solar energy, mechanical energy (hydropower, wind power), and others. Energy sources that cannot be renewed are natural gas energy, coal energy, nuclear, and others. In general, the Atmega16 Microcontroller-Based Solar Tracking System is designed using. ATmega16 Microcontroller, Solar Cell, REED SWITCH Sensor, LDR Sensor, LCD, LED. The microcontroller accepts input from the solar cell, LDR sensor and REED SWITCH sensor, then performs data processing and provides LCD output as a display, LED as an indication of light and power window motor as a solar cell panel drive. This tool serves to increase the efficiency of the solar cell. This tool is made in 1 year. This tool works by following the direction of sunlight. In the presence of sunlight this system will light up. This tool will not stop working while still getting energy from sunlight.